2011
DOI: 10.1080/14927713.2011.549193
|View full text |Cite
|
Sign up to set email alerts
|

Re-imagining institutional spaces: the communitizing potential of leisure

Abstract: In this article, we critically examine an alternative to the theoretical concepts of dividing practices (Foucault, M. (1982). The subject and power. Critical Inquiry, 8,[777][778][779][780][781][782][783][784][785][786][787][788][789][790][791][792][793][794][795] and total institutions (Goffman, E. (1961). Asylums: Essays on the social situation of mental patients and other inmates. Garden City, NY: Anchor Books) by exploring the communitizing potential of long-term care facilities and prisons. In doing so, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Building upon these findings, Norman and Andrews (2019, p. 462) found that prisoners' engagement with sport could facilitate stillness and mental escape, and in so doing help them "cope with the spatial and temporal restrictions placed upon them, both in their regular daily routine and in exceptional circumstances such as being confined to their cells during a lockdown." Research on leisure in prisons (Fortune & Whyte, 2011;Yuen, Arai, & Fortune, 2012), meanwhile, has highlighted the possibility for leisure activities to bring prisoners and community members together in a shared venture and, in so doing, increase the possibility for carceral spaces to "be reimagined as spaces that are vital for promoting commu-nity cohesion and increasing social acceptance" (Fortune & Whyte, 2011, p. 31).…”
Section: Sfd and Compact Forms Of Carceralitymentioning
confidence: 99%
“…Building upon these findings, Norman and Andrews (2019, p. 462) found that prisoners' engagement with sport could facilitate stillness and mental escape, and in so doing help them "cope with the spatial and temporal restrictions placed upon them, both in their regular daily routine and in exceptional circumstances such as being confined to their cells during a lockdown." Research on leisure in prisons (Fortune & Whyte, 2011;Yuen, Arai, & Fortune, 2012), meanwhile, has highlighted the possibility for leisure activities to bring prisoners and community members together in a shared venture and, in so doing, increase the possibility for carceral spaces to "be reimagined as spaces that are vital for promoting commu-nity cohesion and increasing social acceptance" (Fortune & Whyte, 2011, p. 31).…”
Section: Sfd and Compact Forms Of Carceralitymentioning
confidence: 99%
“…One way in which such carceral mobility is manifested is in regular visits by volunteers, who assist with the provision of recreational, spiritual, educational, or therapeutic programs to prisoners. In Canada's federal prison system, for example, over 6,000 community members volunteer with various prison programming (Correctional Service of Canada 2017) and research on leisure programs in women's federal prisons has suggested that volunteers can play a part in building prosocial relationships between community members and prisoners (Fortune and Whyte 2011).…”
Section: Social Interaction Across the Prison Boundary: Yoga Classes As Institutional Displaymentioning
confidence: 99%